2022
DOI: 10.7717/peerj.12841
|View full text |Cite
|
Sign up to set email alerts
|

Potential impacts from simulated vessel noise and sonar on commercially important invertebrates

Abstract: Human usage of coastal water bodies continues to increase and many invertebrates face a broad suite of anthropogenic stressors (e.g., warming, pollution, acidification, fishing pressure). Underwater sound is a stressor that continues to increase in coastal areas, but the potential impact on invertebrates is not well understood. In addition to masking natural sound cues which may be important for behavioral interactions, there is a small but increasing body of scientific literature indicating sublethal physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Although some studies have shown increased activity among blue crabs and American lobsters (Homarus americanus) when exposed to simulated low-frequency vessel noise and mid-frequency sonar (Hudson et al, 2022), or reduced food aggregation in shore crabs (C. maenas) in a field study (Hubert et al, 2018b), recent work on a T-maze (Hubert et al, 2021) demonstrated that the foraging efficiency of shore crabs is not affected by exposing the crabs to a boat sound playback or an ambient control. Our results are in line with this T-maze experiment on shore crabs.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have shown increased activity among blue crabs and American lobsters (Homarus americanus) when exposed to simulated low-frequency vessel noise and mid-frequency sonar (Hudson et al, 2022), or reduced food aggregation in shore crabs (C. maenas) in a field study (Hubert et al, 2018b), recent work on a T-maze (Hubert et al, 2021) demonstrated that the foraging efficiency of shore crabs is not affected by exposing the crabs to a boat sound playback or an ambient control. Our results are in line with this T-maze experiment on shore crabs.…”
Section: Discussionmentioning
confidence: 99%
“…Global vessel noise has increased rapidly over the past several decades [5]. Therefore, the impact of vessel noise on behavior and vocalization in aquatic species [6][7][8][9][10][11][12], including small odontocetes [6][7][8][9], has attracted increasing attention. Over the years, several studies have been performed to elucidate the impact of vessel noise on echolocation clicks.…”
Section: Introductionmentioning
confidence: 99%